2021
DOI: 10.1021/acs.chemrestox.0c00488
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chlorpyrifos on Serine Hydrolase Activities, Lipid Mediators, and Immune Responses in Lungs of Neonatal and Adult Mice

Abstract: Chlorpyrifos (CPF) is an organophosphate (OP) pesticide that causes acute toxicity by inhibiting acetylcholinesterase (AChE) in the nervous system. However, endocannabinoid (eCB) metabolizing enzymes in brain of neonatal rats are more sensitive than AChE to inhibition by CPF, leading to increased levels of eCBs. Because eCBs are immunomodulatory molecules, we investigated the association between eCB metabolism, lipid mediators, and immune function in adult and neonatal mice exposed to CPF. We focused on lung e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 110 publications
1
21
1
Order By: Relevance
“…Ces1d is expressed in mouse alveolar macrophages . In vitro experiments with these cells showed that baseline and LPS-induced levels of PGE 2 and cytokine mRNA (Il6 and TNFa) were higher in alveolar macrophages from Ces1d –/– mice compared to those from WT mice (Figure A).…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Ces1d is expressed in mouse alveolar macrophages . In vitro experiments with these cells showed that baseline and LPS-induced levels of PGE 2 and cytokine mRNA (Il6 and TNFa) were higher in alveolar macrophages from Ces1d –/– mice compared to those from WT mice (Figure A).…”
Section: Resultsmentioning
confidence: 96%
“…Six or twenty-four hours after LPS injection, mice were sacrificed by exsanguination under isoflurane anesthesia (Figure A depicts the experimental protocol). The LPS dose and time points were the same as those in our previous studies. , Blood was collected from the inferior vena cava prior to exsanguination, and serum was prepared by centrifuging the clotted blood (4 °C, 10 min, 3,000 g ). Tissues (lung, liver, and adipose) were immediately flash-frozen in liquid nitrogen and stored at −80 °C until use.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations